Ramadan Fasting Did Not Lessen Vegetable and Fruit Consumption, Sleep Duration, and Physical Activity on Adolescents in Al-Azhar Indonesia University - Afradina Septiasari; Elma Alfiah; Andi Mukramin Yusuf; Amalina Ratih Puspa (Faculty of Public Health Universitas Indonesia, 2023)
AbstractMuslims do Ramadan fasting for around 12 hours (between dawn and sunset). Apart from changing meal times, Ramadan fasting also has the potential to change sleep duration due to sahoor (before the dawn) activities that must be done. The ideal amount and frequency of vegetables and fruit consumption in the national guideline were illustrated by the three main meals a day. The different conditions occurred when doing Ramadan fasting, which was predicted to have less vegetable and fruit consumption than the normal days, especially Muslim adolescents. This research analyzed the difference between the consumption of vegetables and fruit, sleep duration, and physical activity during and after Ramadan fasting among adolescents in Universitas Al-Azhar Indonesia. The research used a quasi-experimental study without a control group, with thirty-five samples. The data collection used a structured 2 x 24-hour recall questionnaire and the Wilcoxon Test to identify the differences. Results showed there were no significant differences between vegetable and fruit consumption, sleep duration, and physical activity during and after Ramadan fasting. Based on the results, the conclusion is that Ramadan fasting had no impact on reducing vegetable and fruit consumption, sleep duration, and physical activity among adolescents in Universitas Al-Azhar Indonesia. Keywords: Adolescent, Ramadan fasting, food consumption. AbstrakUmat muslim melaksanakan puasa Ramadan selama kurang lebih 12 jam (dari matahari terbit hingga tenggelam). Aktivitas puasa Ramadan selain mengubah jam makan, juga berpotensi mengubah pola tidur karena aktivitas sahur yang harus dijalani. Dalam pedoman gizi seimbang, frekuensi konsumsi sayur dan buah digambarkan melalui 3 kali waktu makan utama dalam sehari. Kondisi yang berbeda terjadi saat menjalankan ibadah puasa yang berpotensi dapat mengurangi asupan sayur dan buah dibandingkan hari biasa khususnya pada remaja. Tujuan penelitian ini untuk menganalisis perbedaan antara konsumsi sayur dan buah, durasi tidur, serta aktivitas fisik, saat dan setelah puasa Ramadan pada remaja di Universitas Al-Azhar Indonesia Metode penelitian yang digunakan yaitu metode eksperimen semu tanpa kelompok kontrol, dengan melibatkan 35 mahasiswa/i di Universitas Al-Azhar Indonesia. Pengumpulan data dilakukan dengan teknik wawancara menggunakan kuesioner recall 2 x 24 jam dan menggunakan uji beda Wilcoxon untuk menganalisis perbedaan. Hasil penelitian menunjukkan bahwa tidak terdapat perbedaan yang signifikan antara konsumsi sayur dan buah, durasi tidur, serta aktivitas fisik, saat dan setelah puasa Ramadan.Puasa Ramadan tidak berdampak terhadap penurunan konsumsi sayur dan buah, durasi tidur, serta aktivitas fisik pada remaja di Universitas Al-Azhar Indonesia. Kata Kunci: Remaja, puasa Ramadan, konsumsi makanan